Leaf litter addition experiments in riparian ponds with different connectivity to a Cerrado stream in Mato Grosso, Brazil - Wantzen, K. M.; Rosa, F. R.; Neves, C. O.; Cunha, C. Nunes da (Amazoniana, 2005)
Using standardized artificial substrates (bricks and nylon nets), we analyzed the effect of different treatments on benthic invertebrate colonization in ripanan ponds of a Cerrado stream in Mato Grosso, Brazil.
Keywords: Cerrado